What Drives Emissions Intensity in Azerbaijan’s Light Industry? Evidence from ARDL with Structural Breaks - Gulaliyev, Mayis; Aliyev, Shafa; Musayeva, Jamila; Zeynalova , Mehriban; Alizade, Talat (International Journal of Energy Economics and Policy, 2025)
The article examines emission intensity drivers in Azerbaijan’s light industry (NACE C13–C15: textiles, apparel, leather) over 2007-2023. Air pollutant intensity is defined as the weight of pollutants per 1 AZN of output (kg/AZN), calibrated where relevant to CO2 intensity. Unit root tests (ADF, Zivot– Andrews) reveal a mix of I(0) and I(1) series, allowing ARDL estimation. Considering shocks from the 2015 exchange rate shift, an ARDL (1,2,1,2,2) with a post-break dummy is estimated. Bounds testing confirms cointegration (F = 12.83). The error correction coefficient (−1.90) indicates rapid adjustment to long-run equilibrium. Long-run results show that currency depreciation raises emission intensity, while sectoral productivity lowers it, consistent with scale effects. Exports have a weak negative impact. In the short run, depreciation raises intensity immediately but partially corrects after one year; output growth mitigates the effect. Model checks (LM, RESET, CUSUM, CUSUMSQ) confirm robustness in a small sample. Policy implications suggest that exchange rate shocks temporarily worsen environmental outcomes, whereas expansion and modernization reduce intensity. Priorities include boosting energy efficiency, strengthening cleaner production, and expanding exports to improve environmental performance.